2002
DOI: 10.1034/j.1398-9995.2002.23732.x
|View full text |Cite
|
Sign up to set email alerts
|

Pru p 3 (LTP) content in peach extracts

Abstract: We have developed a system to determine the concentration of LTP in peach extracts. LTP in peel extracts is approximately seven times greater than in pulp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 16 publications
6
42
2
Order By: Relevance
“…In fact, patients monosensitized to LTP, but with only local or mild reactions to Rosaceae fruits, have already been reported both in central European [37] and in Spanish populations [17]. Nevertheless, it has been previously documented that Pru p 3 concentration is approximately 7 times higher in peel than in peach pulp [38] and in our study SPT mean wheal diameter to peach peel showed significant correlations with symptom severity.…”
Section: Discussioncontrasting
confidence: 36%
“…In fact, patients monosensitized to LTP, but with only local or mild reactions to Rosaceae fruits, have already been reported both in central European [37] and in Spanish populations [17]. Nevertheless, it has been previously documented that Pru p 3 concentration is approximately 7 times higher in peel than in peach pulp [38] and in our study SPT mean wheal diameter to peach peel showed significant correlations with symptom severity.…”
Section: Discussioncontrasting
confidence: 36%
“…The authors showed that certain apple strains contained larger amounts of Mal d 1 than others and concluded that the IgE-binding potency of different apple strains correlated with the amount of the allergen. Similar findings were made for the lipid transfer protein, Pru p 3, the major allergen of peach [70]. The concentration of lipid transfer protein Pru p 3 in peach peel extracts was approximately 7 times greater than in pulp extracts [70].…”
Section: The Importance Of the Expression Level And The Amount Of A Psupporting
confidence: 60%
“…Similar findings were made for the lipid transfer protein, Pru p 3, the major allergen of peach [70]. The concentration of lipid transfer protein Pru p 3 in peach peel extracts was approximately 7 times greater than in pulp extracts [70]. …”
Section: The Importance Of the Expression Level And The Amount Of A Psupporting
confidence: 60%
“…LTPs purified from peach and apple were used for skin prick testing of 47 Spanish patients with peach allergy: 91% of them had positive SPT to Pru p 3 and 77% to Mal d 3, and strong correlation was found between the skin responses to the fruit extract and the purified allergen [53]. Similarly, 20 out of 24 (83%) peach-allergic patients with positive SPT to peach skin extract had positive SPT results to the purified LTP [50]. Fernandez-Rivas et al [40] also found that a positive result to SPT with purified Pru p 3 was related to the clinical expression of peach allergy, because it was found in 62% of patients with peach allergy confirmed by DBPCFC and in only 31% of patients whose history of reactions to peach was not confirmed by oral challenge.…”
Section: New Tools For Diagnosismentioning
confidence: 95%
“…Due to their role in plant defence, LTPs are found particularly in the outer layers of plant organs and fruits: it is known that in peaches LTP concentration is about seven times greater in the skin than in the flesh, accounting for 25% of the total protein content of skin [50], and that peach skins are more allergenic than the flesh [51], so that chemical peeling of peach is up to now the only effective treatment to reduce peach allergenicity in industrial products [46].…”
Section: Resistance To Treatmentsmentioning
confidence: 99%